2016
DOI: 10.2174/1568026616666160608084834
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Targeting Drugs for the Treatment of Schizophrenia: Past, Present and Future

Abstract: Schizophrenia is a chronic and debilitating neuropsychiatric disorder affecting approximately 1% of the world’s population. This disease is associated with considerable morbidity placing a major financial burden on society. Antipsychotics have been the mainstay of the pharmacological treatment of schizophrenia for decades. The traditional typical and atypical antipsychotics demonstrate clinical efficacy in treating positive symptoms, such as hallucinations and delusions, while are largely ineffective and may w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
141
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(157 citation statements)
references
References 159 publications
3
141
0
Order By: Relevance
“…The number of predicted targets for each drug are shown in Figure 2 by the light-shaded portions of the bars. Notably, 75 (out of 368) predicted pairs are consistent with already published experimental data [50][51][52]. Table 1 lists 20 of them, along with the corresponding experimentally measured binding affinities; and others can be seen from the entries in Supplementary Table S4 where experimental binding affinities are listed.…”
Section: Figure 1 Space Of Autophagy Modulators and Their Targets (A)supporting
confidence: 73%
“…The number of predicted targets for each drug are shown in Figure 2 by the light-shaded portions of the bars. Notably, 75 (out of 368) predicted pairs are consistent with already published experimental data [50][51][52]. Table 1 lists 20 of them, along with the corresponding experimentally measured binding affinities; and others can be seen from the entries in Supplementary Table S4 where experimental binding affinities are listed.…”
Section: Figure 1 Space Of Autophagy Modulators and Their Targets (A)supporting
confidence: 73%
“…Targeting this pathway are typical antipsychotic drugs, also called first-generation antipsychotic drugs, which are reported to effectively attenuate positive symptoms of schizophrenia by blocking dopamine D 2 receptors on postsynaptic neurons [6]. However, because of their high affinity for dopamine D 2 receptors, typical antipsychotic drugs are associated with a high risk of extrapyramidal motor adverse effects [7].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been reported that anti‐inflammatory agents have antipsychotic effects and are beneficial for schizophrenia patients (Müller et al, 2010; Müller and Schwarz, 2008). Moreover, typical antipsychotics have demonstrated clinical efficacy in the reduction of positive symptoms, but are ineffective and may exacerbate negative symptoms and cognitive deficits associated with schizophrenia (Li et al, 2016). In this regard, the modulation of the astroglial inflammatory response by risperidone may improve its antipsychotic effectiveness, while haloperidol may potentiate the neuroinflammation associated with neuropsychiatric disorders, which in turn could lead to brain damage and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Antipsychotics are medications used in the treatment of neuropsychiatric disorders, such as schizophrenia. These medications can be classified as typical (first generation) and atypical (second generation), according to the receptors to which they bind (Li et al, 2016; Meltzer, 2013; Stockmeier et al, 1993). Chlorpromazine and haloperidol are well‐known typical antipsychotics, while clozapine, quetiapine and risperidone are common atypical antipsychotics (Li et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation